How Zambia and China Co-Created a Debt "Tragedy of the Commons" - Deborah Brautigam (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
Zambia's debt difficulties hit headlines in November 2020 when the country defaulted on its Eurobond payments. In August 2021 a new president, Hakainde Hichilema, took office, facing a debt burden that had never been fully transparent to Zambia's public and the world. In this Working Paper, CARI Director Deborah Brautigam analyzes how Chinese creditors, contractors, and Zambian stakeholders failed to take steps to make Zambia's borrowing sustainable. Curious why Zambia was a clear outlier, the author explores the system for project development and loan approval in Zambia and China.
Keywords: 330